Education as a Principal Instrument for Women’s Emancipation: Malimouna as a Case Study in Rebelle of Fatou Keita - Akintoye, Festus Ayodimeji; Yusuf, Hauwa Labo (African Journal of Stability and Development (AJSD), 2019)
The ultimate goal of education is change that makes society better, but societal view that women occupy a subordinate position in relation to men has been at the centre of academic discourse over the past decades. As women began to progress educationally, they were empowered to do certain things and gradually emancipate from some unpleasant and degrading positions. Education is a means through which one is made conscious and exposed to know all that is happening around oneself. In this work, we are going to see the role that education plays in the life of a woman whose name is Malimouna. She decides to fight against suffering and oppression of women at all levels and to reduce the absolute power of men against women. It is through her exposure and education that she is able to challenge the extreme hegemonic and patriarchal beliefs that men hold against women in her village. She shows that women are wise beings just as men; and as such that they are also capable of changing the political, economic and social situations at any time. The study supports the womanist theory formulated by Chikwenye Ogunyemi and Mary E. Kolawole who are proponents of liberation of African women from the patriarchal yoke while advocating for the compromise and conciliation between men and women. Malimouna believes that women should liberate themselves from the prison of total subordination and should not be yes-men to all irrationalities which the society, nature, phallocentric system, or any belief whatsoever. Because of this, this article examines the role Malimouna plays to free herself and other women from the hegemony of men.